(untitled) (Journal of Medicine, 2022)
Background: Acute pancreatitis (AP) is a significant cause of acute abdominal pain, morbidity andhospitalization. Knowing the details of the clinico-pathological presentation and outcome of the diseasemay aid the better understanding of the disease.Objective: The study was designed to assess the clinico-pathological profile and to estimate immediatehospital outcome of acute pancreatitis patients admitted into a tertiary care hospital. Materials and Methods: This hospital based cross-sectional type of observational study was conductedat Dhaka Medical College Hospital (DMCH), for one-year period (June 2018-May 2019).Total 106established cases of acute pancreatitis were included in this study. Data was analyzed by the SPSS 22Windows version and graph & chart were expressed by using SPSS 22 and MS Excel. The Result waspresented with tables and charts. Results: Among 106 patients, mean age of the patients was 42.5 ±11.3 SD (years), with male predominance(male: female-1.2:1). All of the patients complained abdominal pain (100%) while anorexia (48.1%), 43.4%had vomiting and 31.1% had fever. Regarding clinical signs, abdominal distension (45.3%), paralytic ileus(34.9%) and dehydration (43.4%) were found to be the major clinical signs. The common location of painwas in epigastric region (73.6%) with radiation to back in 20.8% patients. Pain was severe agonizing innature in 76.4% cases. Of all, gall stone disease (17.0%) was the most prevalent cause. According toAPACHE-II score, 74.5% patients had mild pancreatitis (APACHE-II <8) while according to Glasgowcriteria, 66.0% had mild disease (Glasgow score <3). Mean APACHE-II score was 7.07±2.50 and Glasgowscore was 2.90±2.33. Mean hospital stays were 8.9±3.6 days and NPO (nothing per oral) 4.9±1.9 days.Among the patients, 77.4% patients were alive and mortality rate was 22.6%. Conclusion: Although, a larger portion of the patients had no identifiable cause but gall stone was themost common etiology. Pain commonly located in epigastric region with radiation to back. Of all thecases, more than sixty percent of the patients had mild pancreatitis estimated by APACHE II score andGlasgow score. Mean hospital stays were about 9 days and nothing per oral was about 5 days. Overallmortality rate was 22.6%. J MEDICINE 2022; 23: 24-29